DESIGN OF SOLAR TRACKER SYSTEM USING PHOTOTRANSISTOR - Ahmad Fauzan Adziimaa; Detak Yan Pratama; Nabila Widad Dira Sinatrya; Dewi Sugihartati; Wahyu Nur Handayani (IPTEK The Journal of Engineering, 2021)
Intensity of the sun be an important parameter to determine the potential energy in any region. Nowdays, measurement of solar intensity as a panel solar tracker use many variety of sensors. Phototransistor is one of the light sensors that has a greater light sensitivity compared to other light sensors. The design of the system uses four phototransistor which are placed each of two sensors in the east and west of the panel. Accuracy testing calculated by comparing the measurement results on sensor circuit with Lux Meter as validator. The results have shown that the average of phototransistor error is 1.24% and 1.27% on the east side phototransistor and 0.47% and 0.93% on the west side phototransistor.